The result of multiplying 2 by x plus y times 3 plus 5 times z is equal to 10.
2x + y * 3 + 5 * z = 10
2x + 3y + 5z = 10
or
2 (x + y * 3 + 5 * z) = 10
2x + 2y + 6 + 10 + 2z = 10
2x + 2y + 16 + 2z = 10
I forgot how to do these type of problems of translating algebraic verbal expressions. Can someone please check this and tell me which way is right? If not, can you explain this and correct it for me?
2x + y * 3 + 5 * z = 10
2x + 3y + 5z = 10
or
2 (x + y * 3 + 5 * z) = 10
2x + 2y + 6 + 10 + 2z = 10
2x + 2y + 16 + 2z = 10
I forgot how to do these type of problems of translating algebraic verbal expressions. Can someone please check this and tell me which way is right? If not, can you explain this and correct it for me?